Experimental data and numerical modeling of flashing jets of pressure liquefied gases. Issue 1 (24th April 2020) - Lacome, Jean‐Marc; Lemofack, Cedric; Jamois, Didier; Reveillon, Julien; Duret, Benjamin; Demoulin, Francois‐Xavier
Abstract: In industrial activities involving liquefied pressurized gases (LPG), there are several situations that can lead to hazardous flashing two‐phase jets with toxic and explosive consequences. The objective of this study was to further our comprehension of such phenomena in order to develop tools that will enable operational decisions to be made within the framework of risk assessment. Experimental and numerical models were applied to study the two‐phase jet resulting from any LPG releases. They focus especially on the cooling effect that was evidenced by large‐scale trial experiments on releases of butane and propane carried out during the Flashing Liquids in Industrial Environment project. For LPG release, experimental observations show that the minimum temperature values are far below the boiling temperature. Experimental evidence completed by a new dedicated numerical model (thermodynamic equilibrium model) able to handle both boiling and vaporization phenomena gives a coherent picture of the two‐phase flow behavior after the expansion zone. Experimental data analysis completed by comprehensive numerical simulations provides evidences that the system formed by air, vapor, and liquid droplets tends to reach an equilibrium locally.